Community-level prejudice and mortality among immigrant groups. (February 2018) - Morey, Brittany N.; Gee, Gilbert C.; Muennig, Peter; Hatzenbuehler, Mark L.
Abstract: This study assesses whether anti-immigrant prejudice at the community level is prospectively associated with mortality. We used 10 waves of data from the General Social Survey (GSS) that were linked to mortality data via the National Death Index (NDI) for the period between 1993 and 2014 (n = 13, 242). The 2014 GSS-NDI dataset is a nationally representative sample reporting social characteristics and attitudes in the United States that was prospectively linked to mortality data. Community-level prejudice was measured with 5 questions regarding anti-immigrant sentiments across 123 communities, defined using primary sampling units. Cox proportional hazards models tested the association between anti-immigrant prejudice and mortality hazard, controlling for covariates at the individual and community levels. Findings showed that among "other race" respondents, those born in the US had higher risk of mortality in communities with greater anti-immigrant prejudice, whereas foreign-born "other race" respondents had lower risk of mortality in communities with greater anti-immigrant prejudice. Sensitivity analyses indicated that the "other race" category was comprised largely of Asians and Hispanics, and that these results were similar for both groups. In contrast, anti-immigrant prejudice was not associated with mortality for foreign-born immigrants who self-report as white or black. We provide various hypotheses for why US-born immigrant groups seem to suffer higher mortality risk, while foreign-born immigrant groups do not, when they live in communities with high levels of prejudice. Highlights: Examines whether structural anti-immigrant prejudice is associated with mortality. Demonstrates the importance of considering race and nativity simultaneously. Contributes to our understanding of how societal prejudice impacts immigrant groups.